Chaotic attractors and fixed point methods in piecewise fractional derivatives and multi-term fractional delay differential equations - Sumati Kumari Panda; Thabet Abdeljawad; Fahd Jarad (Results in Physics, 2023)
Using generalized cyclic contractions, we establish some fixed point results in controlled rectangular metric spaces. Some subsequent outcomes are obtained. Moreover, some necessary conditions to demonstrate the existence of solutions for the multi-term fractional delay differential equations with wth order and the piecewise equations under the setting of non-singular type derivative are established in this paper. In order to demonstrate the effectiveness of our results, we provided some numerical examples.